A Novel Approach for the Synthesis of Biologically Important N-Aryl Amides with Arenediazonium Salts - Bhojane, Jeevan Manohar; Jadhav, Vilas Gangadhar; Nagarkar, Jayashree Milind (Synthesis, 2014)
A novel protocol has been developed for the synthesis of N-aryl amides from arenediazonium salts and primary amides. Tetrabutylammonium iodide was used as an iodide source for in situ formation of iodobenzene. The reaction was catalyzed by using inexpensive copper(I) iodide. The protocol is widely applicable to a variety of substituted amides and diazonium salts, giving good to excellent yields of the desired products.
Keywords: arylations; diazonium compounds; amides; catalysis; copper